Spectroscopic Studies of Methimazole Reactivity toward the Aquapentacyanoferrate (II) Ion in Aqueous Solutions. Issue 5 (11th July 2012) - Cvijanović Cvijanović, D. D.; Damjanović Damjanović, V. V.; Picek Picek, I. I.; Foretić Foretić, B. B.
Abstract : Methimazole (2-mercapto-1-methylimidazole, MMI) and its pentacyanoferrate (II) complex have been characterized by means of UV/Vis, Raman, and NMR spectroscopy. The reaction of MMI with aquapentacyanoferrate (II), [Fe(CN)5 (H2 O)] 3−, in buffered aqueous solutions yielded the [Fe(CN)5 (MMI)] 3− complex. It was found that only thione tautomer of MMI coordinates to the iron (II). The exceptionally stabile and inert complex was produced.